An Expedient Access to γ‐Ketophosphine Chalcogenides via the Chemo‐ and Regioselective Addition of Secondary Phosphine Chalcogenides to β, γ‐Ethylenic Ketones. Issue 6 (6th August 2015) - Artem'ev, Alexander V.; Malysheva, Svetlana F.; Belogorlova, Nataliya A.; Protzuk, Nadezhda I.; Albanov, Alexander I.; Bagryanskaya, Irina Yu.; Schmidt, Elena Yu.; Gusarova, Nina K.; Trofimov, Boris A.
ABSTRACT: γ‐Ketophosphine chalcogenides, precursors for plethora of novel functionalized phosphine chalcogenides and phosphines, are synthesized by chemo‐ and regioselective addition of secondary phosphine chalcogenides to β, γ‐ethylenic ketones under catalyst‐ and solvent‐free conditions (80–100°C, 8–70 h) in excellent yields. The straightforward superbase‐catalyzed synthesis of starting β, γ‐ethylenic ketones from ketones and acetylenes insures the expedient access to the target γ‐ketophosphine chalcogenides.